Gods and goddesses in ancient Italy - Bispham, Edward; Miano, Daniele (Routledge, 2020)
Cover; Half Title; Title; Copyright; Contents; List of figures; Preface; Introduction; 1 Italic Ceres?; 2 In the name of Diana Feronia and other Italic goddesses in their sacred landscape; 3 Getting to know Diana; 4 Beyond Rome: the cult of Vesta in Latium; 5 The God Castor at Rome: form, function, and cult; 6 Loufir/Liber at the crossroads of religious cultures in Pompeii (third-second centuries BC); 7 Śuri et al.: a 'chthonic' Etruscan face of Apollon?; 8 Honouring honos; 9 From saviours to salvation: Salus in Republican Italy; Index